1989
DOI: 10.1212/wnl.39.11.1509
|View full text |Cite
|
Sign up to set email alerts
|

Progression of hypertensive intracerebral hemorrhage

Abstract: Hypertensive intracerebral hemorrhage (HICH) is generally considered to be a monophasic event. Enlargement of the initial hematoma after several hours or days has rarely been documented. We describe the clinical and CT findings in 8 patients (5 men, 3 women, aged 39 to 68 years) with continued bleeding or rebleeding during the acute phase of HICH. The thalamus was the most frequent site of hemorrhage (6/8). The neurologic status deteriorated in all: 6 within 24 hours, and 2 after 5 and 7 days. Persistent hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(50 citation statements)
references
References 0 publications
3
47
0
Order By: Relevance
“…4,17) Previous data were analyzed without specific statistical methodol ogy, but some recent reports utilized exact statistical analysis. 2,5,7) ICH enlarged in the acute phase in 26% of cases, and thus is not a rare phenomenon.…”
Section: Discussion I Incidence Of Hematoma Enlargementmentioning
confidence: 99%
“…4,17) Previous data were analyzed without specific statistical methodol ogy, but some recent reports utilized exact statistical analysis. 2,5,7) ICH enlarged in the acute phase in 26% of cases, and thus is not a rare phenomenon.…”
Section: Discussion I Incidence Of Hematoma Enlargementmentioning
confidence: 99%
“…A n enlargement of a hematoma (hematoma growth) occurs not uncommonly in patients with spontaneous intracerebral hemorrhage (ICH) after their hospitalization [1][2][3][4][5][6][7][8][9][10][11][12][13] and worsens their clinical outcome. [11][12][13] In our previous review 12 of 419 patients with ICH, we estimated the incidence of hematoma growth (14.3%) and noted the presence of predictors of hematoma growth (viz, a short time interval between admission and onset, an irregularly shaped and large hematoma revealed by an initial CT scan, and liver dysfunction associated with chronic alcohol consumption).…”
mentioning
confidence: 99%
“…Persistent uncontrolled hypertension in acute ICH may increase the risk of ongoing and/or recurrent bleeding from ruptured small arteries and arterioles, leading to haematoma enlargement and clinical deterioration. 36,37 However, the possibility that larger haematomas result in elevated BPs in an attempt to maintain cerebral blood flow in the presence of raised ICP cannot be excluded by these data. A prospective observational study of 103 patients to determine how frequently early growth of ICH occurs failed to identify any significant predictors for haemorrhage growth, including BP.…”
Section: Effects Of Blood Pressure Lowering In Acute Ichmentioning
confidence: 89%
“…34 Based on several relatively small observational studies, it has been suggested that elevated initial BP in ICH is associated with enlargement of haematoma in the period following admission. [35][36][37] Persistent and/or marked elevation of BP has been observed in patients who have been noted to have persistent bleeding or haematoma enlargement on serial CT scans enlargement. Persistent uncontrolled hypertension in acute ICH may increase the risk of ongoing and/or recurrent bleeding from ruptured small arteries and arterioles, leading to haematoma enlargement and clinical deterioration.…”
Section: Effects Of Blood Pressure Lowering In Acute Ichmentioning
confidence: 99%